PERANCANGAN SISTEM KEAMANAN WEBSITE DENGAN KONFIGURASI FILE.HTACCESS - Rico Septiandi; Siti Madinah Ladjamuddin; Ewin Suciana (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2017)
urrently the development of information technology plays a very important role in various aspects of life, the Internet is a global computer network around the world as a medium of communication and modern information that can provide and display various information and data to the public. Website security system with the configuration file.Htacces built with the aim to to protect the website from the theft of information that often occur at this time. This security system is very useful to protect information from cracker attacks. Because data theft on the Internet can not be known if the cracker is taking information without damaging the system. Another case with the theft of information that often occurs in the real world. The design of webste security system is made with the configuration file.Htaccess and Notepad ++. Not a few websites that use a lot of authentication system penetrated by the crackers, they are eyeing this website for allegedly storing confidential information. Need a special way in securing a website like this. With the website security system using the configuration file.htaccess this is one means to secure the website page.